Unlocking insights: Clinical associations from the largest 6-minute walk test collection via the my Heart Counts Cardiovascular Health Study, a fully digital smartphone platform - Kim, Daniel Seung; Schuetz, Narayan; Johnson, Anders; Tolas, Alexander; Mantena, Sriya; O'Sullivan, Jack W.; Hershman, Steven G.; Myers, Jonathan N.; Christle, Jeffrey W.; Oppezzo, Marily; Linos, Eleni; Rodriguez, Fatima; et al. (Progress in cardiovascular diseases, 2025)
The six-minute walk test (6MWT) is a prognostic sub-maximal exercise test used clinically as a measure of functional capacity. With the emergence of advanced sensors, 6MWTs are being performed remotely via smartphones and other devices. The My Heart Counts Cardiovascular Health Study is a smartphone application that serves as a digital platform for studies of human cardiovascular health, and has been used to perform 30,475 6MWTs on 8922 unique participants. As our 30,475 6MWTs represent the largest such collection of data available, we sought to identify associations with measured demographic and clinical variables with 6MWT distance at enrollment and separately determine if use of the My Heart Counts smartphone application led to changes in 6MWT distance. We present the public data release of our 30,475 6MWTs and the launch of a webpage-based data viewer of summary-level statistics, to compare the functional capacity of an individual by their age, gender, height, weight, and disease status (https://mhc-6mwts.streamlit.app). Using multivariable regression, we report associations of demographic and clinical variables with baseline 6MWT distance (N = 3606), validating prior associations with age, male gender, height, and baseline physical activity level with 6MWT distance. We also report associations of 6MWT baseline distance with employment status (+12.4 m ±4.9 m, P = 0.011) and feeling depressed (−3.65 m, ±0.79 m, P < 0.001). We separately found that cardiovascular disease status was significantly associated with decreased 6MWT distance for atrial fibrillation (−24.9 m ±7.8 m, P = 0.0013), peripheral artery disease (−41.7 m ±12.5 m, P < 0.001), and pulmonary arterial hypertension (−76.3 m ±24.8 m, P = 0.0022). Heart failure was associated with decreased 6MWT distance but was not statistically significant (−25.5 m ±14.5 m, P = 0.078). In a subset of participants who conducted repeat 6MWTs separated by at least 1 week but no greater than 3 months (N = 1129), we found that use of the My Heart Counts app was associated with a statistically significant increase in 6MWT distance (+17.5 m ±7.85 m, P < 0.001). We validate previously identified associations from clinic-performed 6MWTs, demonstrating the utility of a mobile method in collecting 6MWT data for clinicians and researchers. We also demonstrate that use of the My Heart Counts app is associated with small, but significant increases in 6MWT distance. Given the importance of 6MWTs in assessment of functional capacity, our publicly-available data will serve an important purpose as a health and disease-specific reference for investigators worldwide.